ACNE VULGARIS AND ITS EFFECT ON QUALITY OF LIFE: A CROSS-SECTIONAL STUDY - Dr. Pallabi Hatikakoty; Dr. Krishna Talukdar; Dr. Minakshi Narah; Dr. Balu Haridas; Dr. Harmeet Singh; Dr. Satyendra Singh (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Acne vulgaris, a widespread dermatological condition, significantly impacts the quality of life of affected individuals, particularly adolescents and young adults. While not life-threatening, its psychosocial and emotional effects can be profound, influencing self-esteem and social interactions. In this study we aimed to look at the proportion of acne vulgaris and its effect on quality of life among patients attending Dermatology OPD in JMCH. Methodology: This one-year, tertiary hospital-based cross-sectional study investigated the impact of acne on 200 patients. The research aimed to determine the prevalence of acne vulgaris among dermatology outpatients at JMCH and to establish an association between acne severity and quality of life. The interview involved detailed patient history, comprehensive cutaneous and psychological examinations, and the recording of disease severity using the Global Acne Grading System (GAGS) score. The Dermatology Life Quality Index (DLQI) questionnaire assessed the impact on quality of life. Results: The study found an average patient age of 24.34 ± 6.29 years, with a predominance of females and facial involvement. While Grade III was the most common grade of acne, the mean GAGS score was 9.98 ± 5.06, indicating that mild acne was most prevalent overall. The average DLQI score was 31.42 ± 25.30, revealing a significant impact on quality of life across participants. Specifically, 24.5% experienced a very large effect, 35.5% a moderate effect, 3.5% an extremely large effect, and 28.5% a small effect on their quality of life. Conclusion: Acne vulgaris extends beyond a cosmetic issue, profoundly affecting emotional and psychological well-being. The study confirms a direct correlation between increased disease severity and a greater impact on quality of life. Effective treatment must therefore address both the physical manifestations and the mental health aspects to improve overall patient outcomes.